Normal or tingly? A story about hands and feet. (2nd January 2022) - Efstathiou, Myrto; Delicato, Louise S.; Sedda, Anna
Abstract: Aims: Spontaneous sensations (SPS) are sensations that are felt in the body in the absence of external stimulation. The literature on SPS has used explicit measures, such as questionnaires to explore SPS, while no studies to date have examined SPS on an implicit level. This study was conducted to collect representative stimuli that can be used to build such a task, for example, an Implicit Association Test. Methods: An online survey was completed by 18 participants to identify the most frequent words used to describe our limbs in the presence or absence of SPS. Results: Individuals who perceive and those who do not perceive SPS in their limbs describe their limbs as normal, while the most frequently described SPS were itching and tingling . Conclusions: Thus, we use the same words/adjectives to describe how we perceive our limbs. However, the way we experience SPS varies as we experience more SPS in hands than feet.